Exploring the electro‐optical properties of conjugated polymers based on oligo‐selenophene and oligo(3, 4‐ethylenedioxyselenophene). (8th May 2019) - Mahdavifar, Zabiollah; Tajdinan, Samira; Shakerzadeh, Ehsan
Abstract : For seeking high‐efficiency narrow‐band‐gap donor materials to enhance short‐circuit current density for organic solar cells, a series of oligo‐selenophene (OS) and oligo(3, 4‐ethylenedioxyselenophene) (OEDOS) with various chain lengths were designed and characterized using density functional theory (DFT) and time‐dependent DFT calculations. Based on the results, it can be seen that with increasing chain length of the oligomers in both syn‐ and anti‐adding manners, the bond length alternation is decreased which indicates that the π‐electron delocalization is increased. Also, when the chain length is increased the electronic energy gap and the optical energy gap are decreased. It can be concluded that the syn‐(OS) n =10, 14, 15, anti‐(OS) n =14 and anti‐(OEDOS) n =7–12 oligomers can act as low‐band‐gap polymers. Therefore they can absorb more sunlight based on maximum wavelength (higher than 620 nm). Furthermore, a red shift in the simulated absorption spectra of (OS) n and (OEDOS) n donors is observed. It is found that (OS) n =14, 15 with syn configuration of the extended oligomers is the most suitable donor for the design of high‐performance organic solar cells possessing a narrow electronic band gap, high exciton lifetime and broad and intense absorption spectra that cover the solar spectrum leading to complete light‐harvesting efficiency. Abstract : A series of oligo‐selenophene (OS) and oligo(3, 4‐ethylenedioxyselenophene) (OEDOS) were designed and characterized using DFT and TD‐DFT calculations.